Re-evaluating the Systematics of Dendrolycopodium Using Restriction-Site Associated DNA-Sequencing - Petlewski, Alaina R.; Hauser, Duncan A.; Kim, Min; Schmutz, Jeremy; Grimwood, Jane; Li, Fay-Wei (Frontiers in Plant Science, 2022)
The genus Dendrolycopodium (Lycopodiaceae) includes four to five species across North America and East Asia. Species identification in Dendrolycopodium is difficult due to limited or inconsistent charac-ters. In addition, plants with intermediate morphologies regularly occur, potentially indicative of inter-specific hybridization. To determine the species relationships in Dendrolycopodium and investigate the existence of hybrids, we generated a draft genome assembly for D. obscurum and carried out double-digest restriction-site associated DNA sequencing (RADSeq) on 86 Dendrolycopodium specimens. Our sampling includes all the described species and 11 individuals with intermediate morphology. We find that the genus can be divided into four clades that largely correspond to the described taxa, as well as evidence of interspecific hybridization. Within these clades, our STRUCTURE analysis suggests that there are multiple finer subgroups, with evidence of hybridization and introgression between these sub-groups. Given the limited availability of specimens collected from Asia, the status of the various Asian species remains uncertain and will require further study. In summary, our study confirms several hy-brid relationships in Dendrolycopodium and provides a clear phylogenetic framework for future taxo-nomic revision.